A Portrayal of Toxic Masculinity in Thanos’s Avengers: Endgame - Nada Novita Sinta Uli Siagian (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
Toxic masculinity is one of the most popular issues related to men in society. One of the factors of toxic masculinity is that men tend to be selfish when they feel better than other men or women in their society. In the Avengers: Endgame, the movie presents human’s war against the villain whose utilization of power to rule the world to attain victory and bring peace to the world by destroying half of the humans. This study used the theory of toxic masculinity by Terry A Kupers so that the toxic masculinity issue can be seen from one of the characters in Avengers: Endgame. Secondly, the researcher attached three steps of power theory by Gaventa’s Theory of Power as the character’s medium to support the relationship between toxic masculinity and power. Next, the researcher focused on one of the villain characters called Thanos, who is identified as the toxic masculinity representation. Qualitative descriptive was the primary method. Then the researcher collected the data by watched the movie, analysed the previous studies, and focused on the dialogue containing direct or indirect toxic masculinity issues. This study explores the features of Toxic Masculinity as portrayed by Thanos and explains the relation of power and toxic masculinity. This study reveals that toxic masculinity leads men to destruction.